The Impact of Corporate Governance Attributes on Environmental Disclosures: Evidence from India. Issue 1 (June 2017) - G., Ezhilarasi; Kabra, K. C.
Abstract: This article empirically investigates the impact of corporate governance attributes on companies' decision to disclose environmental information since corporate governance ensures fair, responsible, credible and transparent corporate behaviours to its stakeholders. The corporate governance attributes used in the study are board size, chief executive officer duality, domestic institutional ownership and foreign institutional ownership. Environmental disclosures are measured by a checklist of items based on Global Reporting Initiative guidelines as well as environmental regulations prevailing in India. Disclosure scores are drawn individually by using content analysis of annual reports for a sample of 177 most polluting companies in India for a period of 6 years, that is, from 2009–2010 to 2014–2015. Employing panel data regression model, the result indicates that foreign institutional ownership is the most important corporate governance attribute that engages corporates in environmental disclosure behaviour. In addition to this, firm-specific characteristics such as company size and environmental certification are more likely to influence environmental disclosures. For better environmental disclosure, the Securities and Exchange Board of India (SEBI) should mandate all the companies to disclose detailed monetary and non-monetary information on environmental issues in their companies' periodic report and also more emphasis should be given to strengthen the corporate governance attributes.